Ecstatic religion: a study of shamanism and spirit possession - Lewis, Ioan M. (Routledge, 2003)
States of spirit possession, in which believers feel themselves to be 'possessed' by the deity and raised to a new plane of existence, are found in almost all known religions. From Dionysiac cults to Haitiam voodoo, Christian and Sufi mysticism to shamanic ritual, the rapture and frenzy of ecstatic experience forms an iconic expression of faith in all its devastating power and unpredictability. Ecstatic Religion has, since its first appearance in 1971, became the classic investigative study of these puzzling phenomena. Exploring the social and political significance of spiritual ecstasy and possession, it concerns the distinct types of functions of mystical experience - in particular, the differences between powerful male-dominated possession cults which reinforce established morality and power, and marginal, renegade ecstatics expressing forms of protest on behalf of the oppressed, especially women.